Assessment of Guidance and Counseling Program Using CIPP and Kirkpatrick Frameworks: A Case Study at SMTK Pekanbaru - Luas, Gracela Natasha; Dwikurnaningsih, Yari; Nugroho, Dwi Yulianto (FKIP Universitas Lampung, 2024)
Assessment of Guidance and Counseling Program Using CIPP and Kirkpatrick Frameworks: A Case Study at SMTK Pekanbaru. Objective: This study aims to evaluate the comprehensive Guidance and Counseling (GC) program using the CIPP evaluation model (Context, Input, Process, Product), combined with the Kirkpatrick evaluation model (Reaction & Outcomes). Method: Data validation was conducted using source triangulation and technique triangulation. The data analysis techniques included data collection, data presentation, data reduction, and conclusion drawing. The evaluation results indicated that, the program was designed to meet the needs of students. The research subjects included the principal, the deputy principal for student affairs, GC teachers, dormitory supervisors, parents, and students. The study was conducted at SMTK Pekanbaru. Findings: The findings indicate that the comprehensive GC program is quite effective but requires improvement in several areas, particularly in relation to the actual conditions of students as well as available resources and infrastructure. Conclusion: This program is designed to meet the needs of students. However, improvements in resources and implementation are necessary. Nevertheless, the program has a positive impact, as 87% of students reported satisfaction, and 74% indicated an increase in self-awareness, skills, and academic performance. Keywords: program evaluation, CIPP, kirkpatrick, comprehensive guidance and counseling.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024123